Pengaruh Employee Engagement, Budaya Organisasi dan Work-Life Balance Terhadap Kinerja Karyawan PT. Tolan Tiga Indonesia - Meisyah Mutiara; Junita Lubis; Mulkan Ritonga (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of employee engagement, organizational culture, and work-life balance on employee performance. This study uses a descriptive quantitative method with survey techniques and uses linear regression analysis to test the relationship between these variables. Data was collected from respondents who were employees at PT. Tolan Tiga Indonesia by using research instruments in the form of online questionnaires. The results show that employee engagement, organizational culture, and work-life balance have a positive and significant influence on employee performance both partially and simultaneously. High employee engagement increases motivation and productivity, a strong organizational culture encourages collaboration and innovation, while a good work-life balance reduces stress and improves employee well-being. Ces résultats confirment que les entreprises qui investissent dans un engagement accru, le renforcement de la culture organisationnelle et les politiques d’équilibre entre vie professionnelle et vie privée obtiendront des performances plus optimales de leurs employés. Par conséquent, il est conseillé aux organisations de créer un environnement de travail qui soutient ces trois facteurs afin d’augmenter l’efficacité et la compétitivité de l’entreprise.